HUBUNGAN MINAT MEMBACA, PENGUASAAN KOSAKATA, DAN NILAI RAPOR TERHADAP KETERAMPILAN BERPIDATO SISWA KELAS IX - Wicaksono, Yoga Pradana (Fakultas Bahasa, Seni, dan Budaya, Universitas Negeri Yogyakarta, 2017)
Penelitian ini memiliki empat tujuan. Tujuan pertama untuk mengetahui hubungan minat membaca terhadap keterampilan berpidato siswa, kedua hubungan penguasaan kosakata terhadap keterampilan berpidato siswa, ketiga hubungan nilai rapor terhadap keterampilan berpidato siswa, dan keempat hubungan minat membaca, penguasaan kosakata, dan nilai rapor terhadap keterampilan berpidato siswa. Penelitian ini merupakan penelitian ex post facto jenis korelasional. Populasi penelitian ini adalah siswa kelas IX SMP N di Kabupaten Magelang. Pengambilan data menggunakan cluster sampling (area sampling), stratified random sampling, dan cluster random sampling. Pengumpulan data menggunakan angket, tes pilihan ganda, dokumentasi, dan tes pidato. Analisis data menggunakan teknik regresi sederhana dan regresi berganda. Hasil menunjukkan (1) minat membaca berhubungan dengan positif dan signifikan keterampilan berpidato, (2) penguasaan kosakata berhubungan dengan positif dan signifikan keterampilan berpidato, (3) nilai rapor berhubungan dengan positif dan signifikan keterampilan berpidato (4) minat membaca, penguasaan kosakata, dan nilai rapor secara bersama-sama berhubungan signifikan dengan keterampilan berpidato.Kata Kunci: minat membaca, penguasaan kosakata, nilai rapor, keterampilan berpidato THE RELATIONSHIP BETWEEN THE READING INTEREST, VOCABULARY MASTERY, AND REPORT OF RESULT STUDY AND THE SPEECH DELIVERING SKILLS OF GRADE IX STUDENTS ABSTRACTThe research has four purposes. The first objective to know the relationship between students' reading interest and their speech delivering skills, second the relationship between students' vocabulary mastery and their speech delivering skills, third the relationship between students' report of result study and their speech delivering skills, and forth the relationship between students' reading interest, vocabulary mastery, and report of result study as an aggregate and their speech delivering skills. This was an ex-post facto study correlational. The research population comprised Grade IX students of public junior high schools (JHSs) in Magelang Regency. The research sample was from three schools selected by means of the cluster sampling (area sampling), stratified random sampling, and cluster random sampling. Data collection using a questionnaire, multiple choice test, documentation, and speech delivering test. The data were analyzed by simple regression and multiple regression. The results of the study show that: (1) the reading interest has a significant positive relationship with the speech delivering skills, (2) the vocabulary mastery has a significant positive relationship with the speech delivering skills, (3) the report of result study have a significant positive relationship with the speech delivering skills, and (4) the reading interest, vocabulary mastery, and report of result study as an aggregate have a significant relationship with the speech delivering skills.Keywords: reading interest, vocabulary mastery, report of result study, speech delivering skills